Failed/difficult Intubation comparing between pre-COVID-19 and COVID-19 pandemic period using a national insurance claims database and information system of a university hospital - Sumidtra Prathep; Alan F. Geater; Hutcha Sriplung; Ponlagrit Kumwichar; Virasakdi Chongsuvivatwong (BMC Anesthesiology)
Abstract Introduction Endotracheal intubation can be difficult or even fail under certain patient and anaesthesiologist conditions. During the COVID-19 pandemic a country-wide lockdown policy was enforced in Thailand which stipulated that anaesthesiologists wear personal protective equipment, powered air purifying respirator, or goggles and surgical/N95 mask during the intubation procedure. Thus, an anaesthesiologist’s vision is restricted and grip on the equipment less sure. Under these conditions, the incidence of difficult intubation was expected to increase. Methods This time-series study was based on the aggregated age- and sex-standardized monthly incidence of difficult intubation among all intubated patients whose data were recorded in the national insurance claims database and among patients recorded in the records of a university hospital from January 2018 to September 2022. Changes in incidence of difficult intubation following the implementation of a lockdown policy from 26 March 2020 during the COVID-19 pandemic were explored using negative binomial regression and interrupted linear regression time-series analysis. Results Data of 922,274 individuals in the national database and 95,457 individuals in the university database were retrieved. The overall incidence of difficult intubation in both settings dropped by 25% following lockdown, significantly so in the national database (p < 0.001). At the point of interruption, a significant drop in level was evident in the national data (of 1.682 per thousand per month, P = 0.003) and a non-significant drop at the university level (of 1.118 per thousand per month, P = 0.304). Discussion The decreased incidence of difficult intubation during the lockdown period was contrary to expectation but might be related to the deployment solely of anaesthesiologists and more experienced anaesthetic staff using videolaryngoscopes during lockdown following the recommendation for intubation during respiratory disease pandemics.